Is There A Correlation Between Social Capital and Well-Being? A Case Study of Urban and Rural Communities in Indonesia - Tri Wahyu Nugroho; Nuhfil Hanani; Sujarwo; Hery Toiba (HABITAT, 2022)
The third goal of sustainable development is the well-being of society. Government actions to achieve this goal is by increasing built capital (e.g., infrastructure and housing) in urban and rural areas. Other forms of capital that can improve well-being include strengthening community bonds in the community (social capital). This study aims to explore the level of social capital (bonding, bridging, and linking) in rural and urban communities and the correlation between social capital and well-being. The data used is the Indonesian Family Life Survey 5 (IFLS5). The sample consists of 12,872 rural communities and 18,532 urban communities. T-test analysis was used to determine differences in levels of social capital, while a pairwise correlation was used to determine the correlation between social capital and well-being. The results showed that the majority of urban and rural communities had moderate levels of bonding and bridging, while linking is at a low level. In addition, there are significant differences in bonding, bridging, and linking social capital between urban and rural communities, in which rural communities have higher scores than urban communities. It was also found that there was a positive relationship between the bridging and bonding of urban and rural communities and well-being.